Carcinoembryonic antigen directed PET−CECT scanning for postoperative surveillance of colorectal cancer. (3rd October 2017) - Vallam, K. C.; Guruchannabasavaiah, B.; Agrawal, A.; Rangarajan, V.; Ostwal, V.; Engineer, R.; Saklani, A.
Abstract: Aim: During the follow‐up of surgically resected colorectal cancer (CRC), positron emission tomography–contrast‐enhanced computed tomography (PET–CECT) is indicated for asymptomatic elevation of carcinoembryonic antigen (CEA) > 5 ng/ml and no obvious site of recurrence on clinical examination and basic imaging. As an institutional policy, a PET–CECT scan was performed at our institute whenever (1) CEA levels rose above 5 ng/ml and (2) CEA values were doubled (even if the CEA level was < 5 ng/ml). Our aim was to correlate the range of CEA elevation with recurrence rates and to evaluate the diagnostic utility of PET–CECT scanning in this setting. Method: We retrospectively analysed all cases where a PET–CECT scan was performed for elevated CEA levels during surveillance visits after complete resection of the primary tumour followed by adjuvant therapy. This study was conducted from 1 January 2013 to 31 July 2015. Results: In all, 104 patients underwent a PET–CECT scan for rising CEA values, and 62 patients (59.6%) were found to have recurrent disease. At CEA levels < 5, 5.1–10, 10.1–15, 15.1–50 and > 50 ng/ml, disease recurred in 10%, 45%, 70%, 94% and 100% patients, respectively. Sensitivity, specificity, positive predictive value and negative predictive value of the PET–CECT scan were 92.7%, 95.2%, 96.2% and 90.9%, respectively. Elevation of CEA levels during follow‐up was indicative of recurrence in 68% of the secretors and 45% of the non‐secretors (based on baseline CEA status). Conclusion: In the setting of rising CEA levels during follow‐up of patients with CRC, a PET–CECT scan is a valuable tool to detect recurrence, irrespective of the baseline CEA secretor status. The likelihood of recurrence of disease was directly proportional to the value of the raised CEA level.